Lumpur Lapindo Dan Psikologis Anak: (Analisis Dampak Bencana Lumpur Lapindo terhadap Perkembangan Psikologis Anak di Tanggulangin Sidoarjo) - Suwarni Suwarni (Journal An-Nafs: Kajian Penelitian Psikologi, 2018)
This research aims to (1) to know the influence of harmony of Lapindo mudflow victim's family to child psychology, (2) to know the influence of social relation to child psychological development, (3) to know the influence of government role on psychological development of child, (5) To know the influence of family harmony, social relations and the role of government on psychological development of child victims of Lapindo through personality of children in Tanggulangin Sidoarjo. This research uses mixed methods. This study uses statistical analysis through multivariate regression analysis, also conducted exploration and narration on the psychological development of children due to Lapindo mud. The results showed that (1) factors that play a role in the achievement of the psychological development of children impact of mud disaster, that is personality factor. Personality has the greatest and meaningful contribution in achieving the child psychological development that is equal to 9, 021%, (2) personality of the child is the factor which most plays role in the development of thinking, development of intelligence, language development, personality development, and development of soul of child religion. Psychologically developing children are independent learners, their awareness and learning abilities are high so that they learn and work on their own to achieve achievement without having to be asked by others, (3) the government's role has to do with the child's psychological development due to Lapindo mud. Child psychology increases if the support from the government is good, contrary, the less the role of government then the psychological child is reduced